2020
DOI: 10.1111/ggi.13941
|View full text |Cite
|
Sign up to set email alerts
|

Working for only financial reasons attenuates the health effects of working beyond retirement age: A 2‐year longitudinal study

Abstract: AimThe health benefits of paid employment in late life are understood, but they might vary according to work motives. We examined the health effects of employment among older adults, focusing on motivation.MethodsWe carried out a 2‐year longitudinal survey from 2013 (baseline) to 2015 (follow up). Among 7608 older adults, the analysis included 1069 who completed both surveys and were employed at baseline. Work motives were assessed using a questionnaire. Participants were assigned to groups based on their resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 20 publications
0
22
1
Order By: Relevance
“…However, other dimensions of employment, such as psychosocial factors (e.g., satisfaction, demand and responsibility), can affect mortality risk. Another factor that should be considered is the motivation to engage in work, as a study showed that older adults who worked only for financial benefits demonstrated a decline in self‐rated health and higher‐level functional capacity 38 . Moreover, the trajectory of occupation and the longest‐held occupation may be linked to occupational status in old age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other dimensions of employment, such as psychosocial factors (e.g., satisfaction, demand and responsibility), can affect mortality risk. Another factor that should be considered is the motivation to engage in work, as a study showed that older adults who worked only for financial benefits demonstrated a decline in self‐rated health and higher‐level functional capacity 38 . Moreover, the trajectory of occupation and the longest‐held occupation may be linked to occupational status in old age.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that should be considered is the motivation to engage in work, as a study showed that older adults who worked only for financial benefits demonstrated a decline in self-rated health and higher-level functional capacity. 38 Moreover, the trajectory of occupation and the longest-held occupation may be linked to occupational status in old age. A future review should focus on these aspects of late-life employment.…”
Section: Discussionmentioning
confidence: 99%
“…We never insist that people should retire early, because employment can provide both health and financial benefits to older adults. For instance, longitudinal analyses of older Japanese suggested beneficial effects of employment on health (Okamoto et al, 2018); however, working for only financial reasons could attenuate such health effects (Nemoto et al, 2020). Nonetheless, raising the retirement age is considered to be inevitable in aging societies.…”
Section: Discussionmentioning
confidence: 99%
“…Age and years of membership were used as continuous variables. A work motive for nancial reward is associated with reducing health bene ts through working in old age [24].…”
Section: Covariatesmentioning
confidence: 99%